Cellular Senescence: A Pathogenic Driver for Pulmonary Fibrosis - Sihan Wang; Rongrong Wang; Qiyuan He; Yicheng Ma; Yanyuan Fang; Jin Yang; Hui Zhao; Lin Fu; Danlei Chen (Frontiers in Bioscience-Landmark)
Pulmonary fibrosis is a life-threatening progressive lung disease characterized by increased fibrogenesis and decreased lung function. Pulmonary fibrosis has a poor prognosis and a low patient survival rate, with no effective treatments currently available. Cellular senescence is thought to contribute to the pathogenesis of this aging-related disease. Cellular senescence and premature aging are involved in the development of pulmonary fibrosis, which affects various cellular processes such as proliferation, apoptosis, and inflammatory responses. Multiple pathways contribute to cellular senescence and participate in the pathogenesis of pulmonary fibrosis, such as tumor protein p53 (p53)/cyclin dependent kinase inhibitor 1A (p21) and cyclin dependent kinase inhibitor 2A (p16)/retinoblastoma protein (pRB). However, many unanswered questions remain concerning the relationship between cellular senescence and pulmonary fibrosis. In this review, we first summarize the common causes of lung cell senescence and pulmonary fibrosis, including aging, inflammation, chemotherapy drugs, and environmental pollutants. We also discuss the enriched signaling pathways and epigenetic factors (e.g., non-coding RNAs) that are important during cell senescence and the progression of pulmonary fibrosis. Finally, we discuss current strategies for treating pulmonary fibrosis by targeting cellular senescence, including relevant preclinical and clinical studies. This review provides new mechanistic insights for understanding the role of cellular senescence in the development of pulmonary fibrosis and its treatment by targeting cellular senescence.